2012
DOI: 10.1002/poc.3032
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on the 13C NMR chemical shifts of the imine carbon in N‐(4‐X–benzylidene)‐4‐(4‐Y–styryl) anilines

Abstract: dLong-range electronic substituent effects were targeted using the substituent dependence of d C (C═N), and specific cross-interactions were explored extendedly. A wide set of N-(4-X-benzylidene)-4-(4-Y-styryl) anilines, p-X-C 6 H 4 CH═NC 6 H 4 CH═CHC 6 H 4 -p-Y (X = NMe 2 , OMe, Me, H, Cl, F, CN, or NO 2 ; Y = NMe 2 , OMe, Me, H, Cl, or CN) were prepared for this study, and their 13 C NMR chemical shifts d C (C═N) of C═N bonds were measured. The results show that both the inductive and resonance effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In previous investigation results of aromatic Schiff base, the coefficients in front of a substituent in the C‐terminal benzene ring are opposite to those in front of the substituent in the N‐terminal benzene ring. However, the coefficients in front of inductive effect parameters and conjugative effect parameters are positive in Eqn , which seems to be in conflict with the previous results.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…In previous investigation results of aromatic Schiff base, the coefficients in front of a substituent in the C‐terminal benzene ring are opposite to those in front of the substituent in the N‐terminal benzene ring. However, the coefficients in front of inductive effect parameters and conjugative effect parameters are positive in Eqn , which seems to be in conflict with the previous results.…”
Section: Resultsmentioning
confidence: 78%
“…Although the correlation result of Eqn is good, there is a large standard deviation. In many previous types of work, it is confirmed that there is an interaction between substituents, and it cannot be ignored. In the investigation of δ C values for p ‐XCAY‐ p , the substituent interaction item, Δ σ 2 was recommended to be divided into two parts: normalΔσF*2 and normalΔσR*2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuvonen pointed out: ‘the presence of the specific cross‐interaction between X and Y could be verified’, but this specific cross‐interaction effect was not be quantified at that time. Recently, Cao et al developed Neuvonen's research by exploring the other properties of XBAYs and proposed the parameter Δ σ 2 to measure the substituent‐specific cross‐interaction effect between substituents X and Y. Here, Δ σ 2 = [ σ x − σ y ] 2 = {[ σ F ( X ) + σ R ( X )]‐[ σ F ( Y ) + σ R ( Y )]} 2 .…”
Section: Introductionmentioning
confidence: 99%